2019
DOI: 10.1002/rcm.8393
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diet composition and tissue type on the stable isotope incorporation patterns of a small‐bodied southern African minnow Enteromius anoplus (Cypriniformes, Cyprinidae)

Abstract: Rationale In trophic ecology, the use of stable isotope data relies on the general understanding of isotope turnover rates and diet‐to‐tissue discrimination factors (DTDFs). Recent studies on the application of stable isotope data have shown that isotope turnover rates and DTDFs can be influenced by many factors, including diet composition and tissue type. This study investigated the influence of diet composition and tissue type on stable isotope incorporation patterns in a small‐bodied African minnow, the chu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
(232 reference statements)
1
8
0
Order By: Relevance
“…Thus, the general fast turnover in muscle compared to fin tissue suggests either differences in protein and lipid content 72 or high muscle turnover compared to fin tissue. Although this observation appeared to be consistent with some studies 38 , 42 , other studies have, nonetheless, reported faster turnover and low isotope enrichment in fin tissues compared to muscle tissue 37 , 63 , 71 . These variations therefore highlight the importance of interspecific differences in isotope incorporation and the need to understand the aspects related to tissue metabolism.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, the general fast turnover in muscle compared to fin tissue suggests either differences in protein and lipid content 72 or high muscle turnover compared to fin tissue. Although this observation appeared to be consistent with some studies 38 , 42 , other studies have, nonetheless, reported faster turnover and low isotope enrichment in fin tissues compared to muscle tissue 37 , 63 , 71 . These variations therefore highlight the importance of interspecific differences in isotope incorporation and the need to understand the aspects related to tissue metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…For example, DeNiro and Epstein 17 showed that trophic enrichment of varied in relation to source values because the metabolic biochemical fractions would directly depend on both the quantity and quality of dietary isotope values. Recent empirical studies on fishes have also shown that different diet sources can yield considerable variation in both tissue turnover rates and 36 , 42 , 62 , 63 . Similarly, an extensive review by Caut et al 29 on several animal taxa reported wide ranging values (− 8.8 to 6.1‰) due to several factors, including diet kinetic effects during catabolism and macromolecule synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations